Problem Gambling
XV, 324 p.
Keywords: Problem gambling is a perennial issue frequently reported in the media. This book is a comprehensive and up-to-date resource on problem gambling research. It describes the state of the art of the subject and presents the latest developments such as computer modelling of gambling behaviour and risk profiles of gambling products.